Paramount Clause and Codification of International Shipping Law - Fernández, Jonatan Echebarria (Journal of maritime law and commerce, 2019)
This article analyses the voluntary inclusion in a charterparty or its incorporation into a bill of lading by the contracting parties of protective clauses such as the Paramount or Himalaya Clauses. The Clauses provide for the application of the Hague-Visby Rules or other international instruments for the limitation of responsibility of the carrier and its servants, agents, and subcontractors. However, the interaction between forum and ius may lead to additional consequences. The validity of the agreement on the applicable law altogether with the choice of seat to solve future disputes between the parties can be limited by public policy and overriding mandatory rules of the forum.